Mini Review: Citrus sinensis Sebagai Bioreduktor Dalam Green Synthesis Nanopartikel - Hiyahara, Irfan Ashari; Hindryawati, Noor; Syaima, Husna; Akbar, Muhammad Marion; Duratulhikmah, Nur Fadhilah; Putra, Narundana Perdana; Wulandari, Siti Aprilia; Larasati, Zarra Udyani; Rahayuningsih, Rahayuningsih; Indriani, Isah Waliah (JURNAL ATOMIK, 2023)
Green synthesis is an eco-friendly approach that provides a viable alternative to traditional physical and chemical methods for the production of nanoparticles. This technique employs non-toxic and safe materials, such as plants, microorganisms, algae, bacteria, yeast, and fungi, to generate stable and less toxic nanoparticles. Citrus sinensis, commonly known as sweet orange, is a plant that contains various active compounds. These bioactive compounds can be extracted and used as bioreductants in green synthesis of nanoparticles. This mini review aimed to provide an overview of the current state of research on the utilization of Citrus sinensis as a bioreductant in the production of nanoparticles. A systematic search strategy was employed to identify research articles that met the criteria of discussing green synthesis of nanoparticles with Citrus sinensis as a bioreductant. The nanoparticles produced using Citrus sinensis extract can be either metal nanoparticles or metal oxide nanoparticles. The review highlights the distribution of nanoparticles produced with Citrus sinensis extract, their applications, and the extraction process of Citrus sinensis commonly employed in green synthesis of nanoparticles. Hopefully this review serves as a useful reference for researchers and practitioners who are interested in employing the Citrus sinensis plant as a bioreductant in the green synthesis of nanoparticles.